EFFECT OF CIDR AND OVSYNCH PROTOCOLS ON ESTRUS RESPONSE, FERTILITY AND PLASMA PROGESTERONE AND BIOCHEMICAL PROFILE IN TRUE ANOESTRUS CROSSBRED COWS* (Indian Journal of Animal Production and Management, 2014)
A study was carried out in the AMUL milk shed area on 30 postpartum crossbred cows, comprising 20 true anoestrus and 10 normal cyclic cows to evaluate clinical response to oestrus induction protocols and plasma progesterone and biochemical profile at different time intervals post treatment/pot-AI. The oestrus induction response obtained with CIDR and Ovsynch protocol in anoestrus cows (10 each) was 100% and 90% with oestrus induction intervals of 6.00 + 3.22 and 86.67 + 3.33 hrs from PG injection, respectively. The conception rates at induced/first oestrus and overall of 3 cycles were 50 and 80% in CIDR 30 and 60% in Ovsynch protocol: and 80% in normal cyclic control cows. The plasma progesterone levels in CIDR protocol on day 0, 7, 9/10 (AI) and day 21 post-AI were 0.65+0.23, 3.48+0.54, 0.48+0.13 and 10.44+1.77ng/ml in conceived and 0.70+0.18, 3.61+1.05, 0.32+0.09 and 1.42+0.38 ng/ml in non conceived cows. The corresponding P4 levels in Ovsynch protocol were 0.28+0.06, 2.98+0.93, 0.48+0.19 and 8.06+1.16 ng/ml in conceived and 0.32+0.07, 3.82+1.35, 0.52+0.30 and 1.24+0.71 ng/ml in non-conceived cows. There was significant cariation in P4 profile between periods in both the protocols (P
Keywords: Crossbred cows; Anoestrus; Oestrus induction/synchronization protocols; Fertility; Progesterone; Metabolites; Conceived and non-conceived groups